Gerakan Literasi Keuangan Melalui Media Menabung Sejak Dini - Amalia, Ananda Rizki; Fatmawat, Lusi; Rahmah, Nur; Nilasari, Raihanisa; Amelia, Tasya (Universitas Pamulang, 2021)
Saving and investment is one indicator in the country's economy that can determine the rate of economic growth. Saving is saving an amount of money so that it can be used in the future if needed. By instilling saving in children from an early age, both by parents (family), teachers (schools) are expected to be able to regenerate the habit of saving in the younger generation. This service is carrying out socialization activities regarding the Saving Movement to the community in RT / RW 006/004 Cipedak village, Jagakarsa District , South Jakarta. This activity aims to provide knowledge and understanding of financial literacy through saving, to foster interest in saving from an early age so that children get used to saving, and by providing examples of how to make piggy banks using used media. This activity is carried out face-to-face (on the spot training) using the method of delivering socialization materials with counseling techniques, questions and answers, quizzes, creation of making piggy banks, and by adding games. The results of children's activities become more knowledgeable about the benefits and tips and know how to make celangan from simple materials. The PKM activity was carried out enthusiastically, as evidenced by their communicativeity in question and answer during the event. This activity is expected to be continued by the surrounding community and be able to regenerate the habit of saving in the next generation of Indonesian youth who in the end will be able to contribute to the nation and state. Keywords: Community Service, Savings, Financial Literacy